Insights into the epigenetics of chronic rhinosinusitis with and without nasal polyps: a systematic review - Brar, Tripti; Marks, Lisa; Lal, Devyani (Frontiers in Allergy, 2023)
Background Epigenetics facilitates insights on the impact of host environment on the genesis of chronic rhinosinusitis (CRS) through modulations of host gene expression and activity. Epigenetic mechanisms such as DNA methylation cause reversible but heritable changes in gene expression over generations of progeny, without altering the DNA base-pair sequences. These studies offer a critical understanding of the environment-induced changes that result in host predisposition to disease and may help in developing novel biomarkers and therapeutics. The goal of this systematic review is to summarize the current evidence on epigenetics of CRS with a focus on chronic rhinosinusitis with nasal polyps (CRSwNP) and highlight gaps that merit further research. Methods A systematic review of the English language literature was performed to identify investigations related to epigenetic studies in subjects with CRS. Results The review identified 65 studies. These have focused on DNA methylation and non-coding RNAs, with only a few on histone deacetylation, alternative polyadenylation, and chromatin accessibility. Studies include those investigating in vivo and in vitro changes or both. Studies also include animal models of CRS. Almost all have been conducted in Asia. The genome-wide studies of DNA methylation found differences in global methylation between CRSwNP and controls, while others specifically found significant differences in methylation of the CpG sites of the thymic stromal lymphopoietin (TSLP), IL-8, and PLAT. In addition, DNA methyltransferase inhibitors and histone deacetylase inhibitors were studied as potential therapeutic agents. Majority of the studies investigating non-coding RNAs focused on micro-RNAs (miRNA) and found differences in global expression of miRNA levels. These studies also revealed some previously known as well as novel targets and pathways such as tumor necrosis factor alpha, TGF beta-1, IL-10, EGR2, aryl hydrocarbon receptor, PI3K/AKT pathway, mucin secretion, and vascular permeability. Overall, the studies have found a dysregulation in pathways/genes involving inflammation, immune regulation, tissue remodeling, structural proteins, mucin secretion, arachidonic acid metabolism, and transcription. Conclusions Epigenetic studies in CRS subjects suggest that there is likely a major impact of the environment. However, these are association studies and do not directly imply pathogenesis. Longitudinal studies in geographically and racially diverse population cohorts are necessary to quantify genetic vs. environmental risks for CRSwNP and CRS without nasal polyps and assess heritability risk, as well as develop novel biomarkers and therapeutic agents.